Secondary iatrogenic duedonum perforation: a rare complication - Özdoğan, Alperen; Ay, Oğuzhan Fatih; Yılmaz, İsmayil (The European Research Journal, 2024)
The incidence of perforations resulting from Endoscopic Retrograde Cholangiography (ERCP) is observed to be less than 1%. In this case report, we aim to present our unique experience as a mechanism, which is even more uncommon. A 68-year-old male with an ASA score of 2 was prediagnosed with a distal common bile duct tumor. ERCP was performed for therapeutic and diagnostic purposes and a 9F 10 cm plastic stent was placed to relieve obstruction. The patient, who had the sudden onset of abdominal pain within the initial 24-hour period following the procedure, underwent surgical intervention subsequent to a computed tomography assessment. In the third portion of the duodenum, an approximately 4 mm perforation originating from the stent was observed during the examination. It was repaired with a 3.0 prolene suture, followed by omentopexy. He was discharged uneventfully on the eighth day. Although duodenal perforation due to the placement of a plastic biliary stent with ERCP is a very uncommon complication, the patient’s clinical and imaging findings are essential for treatment planning.